An observational study to correlate arterial lactate level and peripheral perfusion index in context of tissue perfusion in sepsis - Singla, Priyanka R.; Mahajan, Sanket K. (International Journal of Research in Medical Sciences, 2023)
Background: In view of goal directed therapies, the predictive value of the course of peripheral perfusion parameters over time has not been studied. Moreover serial assessment of peripheral perfusion index (PI) can be more predictive for mortality when compared to a single assessment of peripheral perfusion. Successfully normalized PI (≥1.4) during treatment might be an indication to stop the resuscitation, whereas pursuing normalized PI (≥1.4) might not result in better outcomes compared with mild-to moderate PI impairment after a normalized arterial lactate level. Complementing arterial lactate assessment with PI during resuscitation can better identify the endpoint of resuscitation and patients at higher risk of adverse outcomes. By simple clinical assessment of peripheral perfusion immediately during and after resuscitation, clinicians will be able to discriminate patients at high risk for developing severe complications even in the rural setups. Methods: This prospective study was conducted on 100 patients admitted at Dr. Kiran C. Patel Medical College and Research Institute, over a period of 12months (Janury 2022 to December 2022). Patients of sepsis were selected on the basis of criteria for tissue hypoperfusion and classification of sepsis. Results: On statistical analysis, PI was found to have significant correlation with arterial lactate levels (P<0.001) in PI <1.4 sub-measurement and not in PI >1.4. SOFA score & metabolic parameters were also found to have statistical significance. Conclusions: We inferred that peripheral perfusion index monitoring could provide useful information to determine the possibility of hyperlactatemia in critically ill patients thus providing a noninvasive source of tissue-bed perfusion monitoring even in the absence of facilities and infrastructure to measure the lactate levels thereby providing a gross insight in the perfusion haemodynamics of the patients of sepsis even in the primary healthcare setups too.